Sisa Kehidupan Prasejarah Masa Kini Studi Tradisi dan Budaya di Beberapa Wilayah Nusantara (Kajian Literatur) - Nuraini Mannan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The prehistoric period has ended formally in Indonesia with the discovery of the first writings from around the 4-5th century AD, in many places in Indonesia there are still visible signs of the persistence of prehistoric traditions far into the historical period to the present. Ethnographic sources that describe the lives of several isolated tribes which are somewhat isolated from the pace of the modernization process in this country, contain indications that prehistoric elements still exist in the lives of these communities. Some of these elements that settle in some aspects of socio-economic life and beliefs can be returned to their origins in the farming period. The most prominent among the remnants of that life is the tradition of worshiping ancestors both embodied in megalithic buildings as well as those conceived in the mind, although several religious conceptions such as Hindu-Buddhist, Islam and Christianity in layers form the mind. Indonesian spirituality. The research method used in this paper is a literature study, some related literature according to the context is included in this paper. The purpose of the study is to describe the remnants of prehistoric life in several regions in Indonesia to the present.